Photoluminescence, photoredox properties and crystal structures of rhenium(v)-benzylidyne complex with phosphine ligands. - Verma, Smriti; Verma, Samridhi; Tripathi, P N (International Multidisciplinary Research Journal, 2012)
Several rhenium(v)-benzylidyne complexes [Re(CR)(pdpp)2Cl]+[R=C6H2Me3-2,4,6,pdpp= o-phenylenebis(diphenylphosphine)], [Re(CR)L2(CO)(H2O)Cl]+ [L=PPh3, P(C6H4OMe-p)3 or PMe2Ph] and trans-[Re(CR)(dppe)(CO)2Cl]+ [dppe= 1,2-bis(diphenylphosphino)ethane] have been prepared. The structures of trans-Re(CR)(pdpp)2Cl]ClO4.CHCl3.0.25MeOH and [Re(CR)(PPh3)2 (CO)(H2O)Cl]ClO4. 1.5MeOH have been determined by X-ray analyses. The Re≡C distances are 1.802(5) and 1.784(8) Å respectively. In acetonitrile and dichloromethane the complexes show intense absorption bands at 318-330 nm and weak ones at 405-450 nm, the latter being tentatively assigned to dxy → dn* (dxz,dyz) transitions. Photoexcitation in the solution, solid or glassy state gives intense orange to red emissions, and the emitting states are tentatively assigned to 3[(dxy)1](dπ*)1]. The variation in non-radiative decay rate constants for the emissions of the rhenium(v)-benzylidyne complexes are consistent with a predication from the energy-gap law. The excited states are better oxidants and reductants than the grounds states. The values of E°(Rev*-ReIV ) and E° (ReVI-ReV*) in acetonitrile have been determined using spectroscopic and electrochemical data as well as by Stern-Volmer quenching experiments.